Upotreba ultrakratkodelujućeg selektivnog antagoniste β1-adrenergičkih receptora u hirurgiji uha, nosa i grla - Lončar-Stojiljković, Dragana B.; Maksimović, Žana M; Đurić, Marko (Scripta Medica, 2022)
Background / Aim: The concept of general balanced anaesthesia was devised in order to assure cardiovascular stability and fast post-anaesthesia recovery. This clinical trial was organised in order to investigate the parameters of cardiovascular function and emergence from anaesthesia in elective ear, nose and throat (ENT) surgery patients. Methods: A total of 40 ASA I and II patients of both sexes scheduled for elective ENT surgery were randomly divided into two equal groups. Both groups received a continuous iv infusion of glucose 5 % solution and in the esmolol group this infusion also contained esmolol. Esmolol infusion rate was 0.3 mg/kg/min during the first 5 min and thereafter 0.1 mg/kg/min. In critical phases of anaesthesia and operation (induction, intubation, first incision, surgical manipulations, wound suture, extubation), systolic and diastolic blood pressure were monitored. Recovery after anaesthesia was assessed based on times of eye opening on command, spontaneous eye opening and regaining of full orientation. Increases in cardiovascular parameters by 20 % of the baseline values or more were treated with iv boluses of fentanyl, alone or with droperidol and, if necessary, by adding isoflurane 0.5 % to the inhalational mixture. Consumption of drugs was recorded. Results: Esmolol assured stable values of cardiovascular parameters that were in most critical phases of anaesthesia and operation lower than in the control group. The duration of anaesthesia did not differ between the groups. In the esmolol group, lower consumption of fentanyl, droperidol and sevoflurane was registered. Patients in the esmolol group emerged from anaesthesia faster than patients in the control group. Conclusion: Continuous iv infusion of esmolol assures better cardiovascular stability, necessitates lower consumption of analgesics and anaesthetics and results in faster emergence from general anaesthesia in elective ENT surgery.